2010
DOI: 10.1681/asn.2009121235
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Concentration of Poverty and Arteriovenous Fistula Use among ESRD Patients

Abstract: There is substantial geographic variability in both incident and prevalent arteriovenous fistula (AVF) use among patients with ESRD. This study examined the degree to which these variations associate with poverty in the county of a patient's treatment center. We performed a cross-sectional study including 28,135 patients treated by 1127 hemodialysis centers in five ESRD networks (16 states) between June 1, 2005 and May 31, 2006. We used the 2000 U.S. Census to categorize county-level poverty and ascertained in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 27 publications
3
17
0
Order By: Relevance
“…One recent study reported that patients living in residential areas with a larger proportion of black residents were less likely than those in other areas to have received nephrologist care (26). Another study found that county poverty is associated with the decreased likelihood of AVF use (33). To our knowledge, our study is the first to examine combined urbanization/rurality and racial/ethnic variations in pre-ESRD care at a national level.…”
Section: Discussionmentioning
confidence: 79%
“…One recent study reported that patients living in residential areas with a larger proportion of black residents were less likely than those in other areas to have received nephrologist care (26). Another study found that county poverty is associated with the decreased likelihood of AVF use (33). To our knowledge, our study is the first to examine combined urbanization/rurality and racial/ethnic variations in pre-ESRD care at a national level.…”
Section: Discussionmentioning
confidence: 79%
“…Because AVF require several weeks to mature and approximately 40% of created AVF never mature [4] , AVF creation is reliant on predialysis care, especially predialysis nephrology referral [5][6][7] . While studies of the development and maturation of AVF have focused on clinical factors [8][9][10][11] , the role of socioeconomic factors, particularly individual-level poverty, has not been reported in a recent national cohort of dialysis patients, although a previous study reported that county-level poverty was inversely associated with incident AVF use, but not with subsequent improvement in AVF use in prevalent patients [12] . We have previously reported that AVF use in new HD patients is significantly higher among patients in the federal health system (e.g.…”
Section: Impact Of Poverty and Healthmentioning
confidence: 98%
“…Although the receipt of nephrologist care is influenced by individual as well as contextual factors such as those related to residence, prior studies have mostly examined individual factors (12,(19)(20)(21), or the few studies that examined contextual factors have generally examined them separately (22)(23)(24) or were limited to certain regional areas (15,25). An important knowledge gap exists regarding broad regional (e.g., state-level) differences in the utilization of nephrologist care among patients with CKD stages 4-5.…”
Section: Introductionmentioning
confidence: 99%